Advances in artificial life. Darwin meets von Neumann 10th European Conference, ECAL 2009, Budapest, Hungary, September 13-16, 2009, Revised Selected Papers. Part I - European Conference on Artificial Life Budapest, Hungary) 2009; Kampis, György 1958-; Karsai, Istvan; Szathmáry, Eörs; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
The two-volume set LNAI 5777 and LNAI 5778 constitutes the thoroughly refereed post-conference proceedings of the 10th European Conference, ECAl 2009, held in Budapest, Hungary, in September 2009. The 141 revised full papers presented were carefully reviewed and selected from161 submissions. The papers are organized in topical sections on evolutionary developmental biology and hardware, evolutionary robotics, protocells and prebiotic chemistry, systems biology, artificial chemistry and neuroscience, group selection, ecosystems and evolution, algorithms and evolutionary computation, philosophy and arts, optimization, action, and agent connectivity, and swarm intelligenc
Electronic reproduction.
Keywords: Biological systems -- Computer simulation -- Congresses; Artificial life -- Congresses; Artificial intelligence -- Congresses; Electronic book